2004
DOI: 10.3201/eid1006.030744
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Incidence and Risk Factors amongHelicobacter pylori–Infected Persons, United States

Abstract: Helicobacter pylori is the primary cause of peptic ulcer disease and an etiologic agent in the development of gastric cancer. H. pylori infection is curable with regimens of multiple antimicrobial agents, and antimicrobial resistance is a leading cause of treatment failure. The Helicobacter pylori Antimicrobial Resistance Monitoring Program (HARP) is a prospective, multicenter U.S. network that tracks national incidence rates of H. pylori antimicrobial resistance. Of 347 clinical H. pylori isolates collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
149
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(159 citation statements)
references
References 22 publications
6
149
2
2
Order By: Relevance
“…Immunohistochemistry offers a suitable method for The presence of mutations associated with clarithromycin resistance by melt curve analysis is also shown. 21 In total, nearly half of the patients in our study (50%) were positive for mutations associated with clarithromycin resistance. Although this high percentage is striking in comparison with the HARP study, it is important to note that patients in our study population typically present for biopsy following presumed failure of initial therapy.…”
Section: Discussionmentioning
confidence: 72%
“…Immunohistochemistry offers a suitable method for The presence of mutations associated with clarithromycin resistance by melt curve analysis is also shown. 21 In total, nearly half of the patients in our study (50%) were positive for mutations associated with clarithromycin resistance. Although this high percentage is striking in comparison with the HARP study, it is important to note that patients in our study population typically present for biopsy following presumed failure of initial therapy.…”
Section: Discussionmentioning
confidence: 72%
“…Another study showed that 80% of strains in Mexico were resistant to metronidazole [55] . Overall, metronidazole resistance is > 50% in much of the world but there are reports that metronidazole resistance has declined in Northern Europe [9,30] , while in the United States and Europe, the metronidazole resistance rate was reported to be < 40% [30,56] , and 22.5% in 102 isolates from Norway [57] . However, in Central and Southern Europe, resistance rates remain markedly higher-34.9% in France and 32.7% in Germany [47,58] .…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 99%
“…However, concerns have been expressed regarding the progressive reduction of its efficiency over the past years [6], possibly due to the development of antimicrobial resistance, particularly in the United States and Europe [7,8]. Resistance is variable from country to country, and also within different regions of the same country [9,10].…”
Section: Introductionmentioning
confidence: 99%